2011
DOI: 10.1021/ac200058r
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Highly Sensitive Aptasensor for Potassium with a Nicking Endonuclease-Assisted Signal Amplification Strategy

Abstract: A novel strategy to fabricate an aptasensor for potassium with high sensitivity and selectivity by using nicking endonuclease is proposed in this work. A nicking endonuclease (Nt.CviPII), which may recognize specific nucleotide sequences in double-stranded DNA formed by a potassium-binding aptamer and a linker DNA but cleave only the linker strand, may transfer and amplify the quantitative information of the potassium detection to that of the linker DNA through elaborate strand-scission cycles. Since the techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 33 publications
1
61
0
Order By: Relevance
“…In the assay, a DNA sticky end pair and EcoRImodified nanoparticles were utilized because divalent Mg 2+ is a cofactor to activate EcoRI cleavage of DNA. Li et al [213] demonstrated a colorimetric aptasensor for K + using nicking endonuclease. The detection mechanism is based on the competitive binding of a potassium-specific aptamer to K + and a DNA linker.…”
Section: Increased Aggregate Size: Enzyme-guided Aggregate Formationmentioning
confidence: 99%
“…In the assay, a DNA sticky end pair and EcoRImodified nanoparticles were utilized because divalent Mg 2+ is a cofactor to activate EcoRI cleavage of DNA. Li et al [213] demonstrated a colorimetric aptasensor for K + using nicking endonuclease. The detection mechanism is based on the competitive binding of a potassium-specific aptamer to K + and a DNA linker.…”
Section: Increased Aggregate Size: Enzyme-guided Aggregate Formationmentioning
confidence: 99%
“…The flexible base sequences, isothermal reaction and reduced nonspecific binding properties provided unique features for bioanalytical applications. Specifically, the G-quadruplex-hemin horseradish peroxidase (HRP)-mimicking enzyme has been extensively used as a catalytic label for the amplified colorimetric (Li et al, 2009;Zhu et al, 2011), electrochemical Wang et al, 2014b) or chemiluminescent (Gao and Li, 2013;Luo et al, 2012;Zhou et al, 2012) detection of DNA. By combination with hybridization chain reaction (HCR) to assemble long nanowires or rolling circle amplification strategy, G-quadruplex-hemin complex itself can achieve the signal amplification process efficiently (Cheglakov et al, 2007;Shimron et al, 2012;Wang et al, 2014a;Weizmann et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Unlike most conventional affinity reagents (e.g., antibodies), a group of aptamers called structureswitching aptamers (SSAs) 6 can undergo target-induced conformational change, which is actually the basis of many sensing approaches including fluorescent methods, colorimetric methods, 7,8 and electrochemical methods. 9,10 Biosensing by fluorescence is one of the most popular methods for the design of aptamer-based assays, largely because of the ease of detection, good sensitivity, and potential for highthroughput analysis.…”
mentioning
confidence: 99%